Towards Building Wind Tunnels for Data Center Design - Floratou, Avrilia; Bertsch, Frank; Patel, Jignesh M.; Laskaris, Georgios (PVLDB, 2014)
Data center design is a tedious and expensive process. Recently, this process has become even more challenging as users of cloud services expect to have guaranteed levels of availability, durability and performance. A new challenge for the service providers is to find the most cost-effective data center design and configuration that will accommodate the users’ expectations, on ever-changing workloads, and constantly evolving hardware and software components. In this paper, we argue that data center design should become a systematic process. First, it should be done using an integrated approach that takes into account both the hardware and the software interdependencies, and their impact on users’ expectations. Second, it should be performed in a “wind tunnel”, which uses large-scale simulation to systematically explore the impact of a data center configuration on both the users’ and the service providers’ requirements. We believe that this is the first step towards systematic data center design – an exciting area for future research.